An unusual presentation of inverted papilloma in the nasopharynx - Sarasan, Hena Mithra (International Journal of Research in Medical Sciences, 2025)
Inverted papilloma is a benign epithelial ingrowth into the underlying stroma of the nasal cavity and paranasal sinuses. Even though inverted papilloma is a common lesion within the nasal cavity, it rarely presents primarily in the nasopharynx. This patient presented with clinical features of a nasopharyngeal mass, which on imaging of nose and paranasal sinuses revealed a well-defined polypoidal soft tissue density lesion seen arising from the posterolateral wall of nasopharynx. Total surgical excision of the mass was done and histopathological examination was indicative of inverted papilloma with features suggestive of carcinoma in situ. The importance of early identification of this lesion lies in the fact that the tumor is well known for its invasiveness, tendency to recur and association with malignancy. Hence this requires close surveillance and regular follow up with endoscopy and imaging. This case is rare of its type due to its unusual presentation as an isolated nasopharyngeal mass without extension to nasal cavity.